2019
DOI: 10.1002/hbm.24913
|View full text |Cite
|
Sign up to set email alerts
|

Amisulpride and l‐DOPA modulate subcortical brain nuclei connectivity in resting‐state pharmacologic magnetic resonance imaging

Abstract: The precise understanding of the dopaminergic (DA) system and its pharmacological modifications is crucial for diagnosis and treatment of neuropsychiatric disorders, as well as for understanding basic processes, such as motivation and reward. We probed the functional connectivity (FC) of subcortical nuclei related to the DA system according to seed regions defined according to an atlas of subcortical nuclei. We conducted a large pharmaco‐fMRI study using a double‐blind, placebo‐controlled design, where we exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 81 publications
1
14
0
Order By: Relevance
“…of L-DOPA, a precursor of dopamine synthesis, was found to increase the VTA/SNc functional connectivity with insula(Grimm et al, 2020).Additionally, the finding of increased coupling of the left SNc with the left DLPFC in older adults corresponds well with an earlier report showing the connectivity between VTA/SNc and lateral prefrontal cortex increased with age (18-49 years old; Manza et al, 2015). ACC is involved in the action-outcome learning, and one of the pathways through which it guides the selection of future behaviour leads to the DLPFC (Der-Avakian and Markou, 2012).…”
supporting
confidence: 87%
See 2 more Smart Citations
“…of L-DOPA, a precursor of dopamine synthesis, was found to increase the VTA/SNc functional connectivity with insula(Grimm et al, 2020).Additionally, the finding of increased coupling of the left SNc with the left DLPFC in older adults corresponds well with an earlier report showing the connectivity between VTA/SNc and lateral prefrontal cortex increased with age (18-49 years old; Manza et al, 2015). ACC is involved in the action-outcome learning, and one of the pathways through which it guides the selection of future behaviour leads to the DLPFC (Der-Avakian and Markou, 2012).…”
supporting
confidence: 87%
“…The research in animal models and humans supports the involvement of the dopaminergic system in cognitive functions such as sustained attention (Bellgrove et al, 2005), working memory (Bäckman and Lyberg, 2013), executive control (Saloner et al, 2020), as well as visuomotor search (Chen et al, 2020). Several resting-state studies have found the functional connectivity of VTA and SNc to be related to aspects of reward processing (Adrián-Ventura et al, 2019; Schmaal et al, 2012), impulsivity (Grimm et al, 2020), interoception (Chong et al, 2017) and gait speed (Karim et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is conflicting insight how the dopaminergic system is related to different facets of impulsivity: While a positron emission tomography study of D 2 /D 3 receptor binding found binding in people with high venturesomeness but no effect of impulsiveness ( 49 ), another study found higher limbic availability of the D 2 /D 3 receptor in participants scoring high on non-functional impulsivity (comparable to Impulsiveness) ( 50 ). The UPPS scale is linked to a specific change of midbrain dopaminergic projections to the mid–cingulate gyrus during a dopaminergic challenge ( 51 ). Therefore, an easy-to-apply questionnaire such as the IV7 could be a proxy for a neurobiological state, e.g., dopaminergic responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 160 patients diagnosed with mild to moderate depression between January 2019 and December 2021 were recruited. Patients were included if they (1) met the diagnostic criteria for depression, according to the fifth edition of the American Handbook on Diagnosis and Statistics of Mental Disorders[ 4 , 5 ]; (2) had a score between 17 and 24 points on the 17-item Hamilton depression rating scale (HAMD); and (3) were between 19 and 75 years of age. The exclusion criteria were as follows: history of brain tumor or cerebrovascular disease; cardiac or pulmonary dysfunction; infectious diseases; dementia or Alzheimer’s disease; other mental disorders; history of craniocerebral trauma or surgery; and other serious diseases.…”
Section: Methodsmentioning
confidence: 99%